Aseismic Multifissure Modeling in Unfaulted Heavily Pumped Basins: Mechanisms and Applications. Issue 10 (6th October 2021) - Li, Yueting; Teatini, Pietro; Yu, Jun; Franceschini, Andrea; Frigo, Matteo; Zoccarato, Claudia; Ye, Shujun
Abstract: Aseismic earth fissures are among the most dangerous by‐products of excessive groundwater exploitation in many subsiding sedimentary basins. Improving our understanding of the mechanisms of earth fissuring is important for land planning and risk management. We employ an advanced finite‐element interface‐element modeling approach to understand the generation and propagation of multiple fissures in unfaulted basins. Almost parallel earth fissures at a relative short distance (on the order of tens of meters) generally develop above impermeable and/or incompressible ridges buried by the compacting sedimentary units. Initially, we investigate the effect of the ridge slope on a simplified geological setting sketched from the Luke salt dome, Arizona. Then, we apply the model to the hydrogeologic setting at Guangming village, Wuxi, China. In both analyses, the model simulates the formation of multifissures above the ridge, as observed at the sites. The earth fissures initiate at land surface and propagate downward. They are caused by the combination of tensile stress (bending condition) and shear stress (shearing conditions) accumulation around and above the tip and the slopes of the ridge, respectively. The steeper the ridge, the more concentrated stress zone develops above the ridge tip, favoring the formation of fissures with significant opening and small or null offset. The opposite facilitates a widening of the stress accumulation area, with less‐deep fissures characterized by larger sliding and smaller opening. At Guangming, the model suggests that fissures propagate down to 20–50‐m depth, with maximum opening and sliding of ∼50 cm. Plain Language Summary: Aseismic earth fissures are a major geological hazard often accompanying land subsidence due to groundwater withdrawal. Hundreds of earth fissures have been observed in several alluvial basins of the World. Improving our understanding of the mechanisms of earth fissuring is important for land planning and risk management. We employ an advanced numerical modeling approach to discover the generation and propagation of multiple fissures. Almost parallel earth fissures at a relative short distance generally develop above impermeable and/or incompressible ridges buried by the compacting sedimentary units. We investigate the effect of the ridge slope on a simplified geological setting sketched from the Luke salt dome, Arizona. Then, we apply the model to the hydrogeologic setting at Guangming village, Wuxi, China. In both analyses, the earth fissures initiate at land surface and propagate downward. They are caused by the combination of tensile stress and shear stress accumulation around and above the tip and the slopes of the ridge, respectively. The outcomes indicate the steeper the ridge, the more concentrated stress zone develops above the ridge tip, favoring the formation of fissures with significant opening. The opposite facilitates a widening of the stress accumulation area, with less‐deep fissures characterized by lager sliding. Key Points: Multiple earth fissures develop above buried ridges in subsiding basins An advanced numerical model allows understanding the driving mechanisms A combination of bending and shear stresses causes the formation of nearby multifissures